Procedures and Controls for Arbitration as a Means of Resolving Disputes in Administrative Contracts - Brenkia, Djalila (Journal of Legal Studies and Researches, 2022)
This research paper aim to study the arbitration rules and procedures to settle disputes in the administrative contracts. Since arbitration has become a necessity imposed by reality. That is why the Algerian legislator has to keep pace with this reality through setting obvious legal provisions, which allows the conclusion of an arbitration agreement in administrative contracts.